solve:-3(x-3)=5(2x+1)
Answers
Answered by
0
Simplifying
3(x + -3) = 5(2x + 1)
Reorder the terms:
3(-3 + x) = 5(2x + 1)
(-3 * 3 + x * 3) = 5(2x + 1)
(-9 + 3x) = 5(2x + 1)
Reorder the terms:
-9 + 3x = 5(1 + 2x)
-9 + 3x = (1 * 5 + 2x * 5)
-9 + 3x = (5 + 10x)
Solving
-9 + 3x = 5 + 10x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-10x' to each side of the equation.
-9 + 3x + -10x = 5 + 10x + -10x
Combine like terms: 3x + -10x = -7x
-9 + -7x = 5 + 10x + -10x
Combine like terms: 10x + -10x = 0
-9 + -7x = 5 + 0
-9 + -7x = 5
Add '9' to each side of the equation.
-9 + 9 + -7x = 5 + 9
Combine like terms: -9 + 9 = 0
0 + -7x = 5 + 9
-7x = 5 + 9
Combine like terms: 5 + 9 = 14
-7x = 14
Divide each side by '-7'.
x = -2
Simplifying
x = -2
Answered by
3
refer attachment & mark as brainlist
Attachments:
![](https://hi-static.z-dn.net/files/dde/189d366a3de8eea492ae148103e85774.jpg)
Similar questions
India Languages,
4 months ago
Math,
9 months ago
Science,
9 months ago
Physics,
1 year ago
English,
1 year ago